Blood pressure in postmenopausal women with a history of polycystic ovary syndrome - Doroszewska, Katarzyna; Milewicz, Tomasz; Mrozińska, Sandra; Janeczko, Jarosław; Rokicki, Radosław; Janeczko, Marek; Warzecha, Damian; Marianowski, Piotr (Menopause Review/Przegląd Menopauzalny, 2019)
Polycystic ovarian syndrome (PCOS) is the most common endocrine disorder at reproductive age, affecting 6-10% of females in this group. The aetiology of this syndrome is not fully understood. Genetics, endocrinology factors, and the influence of the environment are possible causes of this syndrome. PCOS is characterised by menstrual disorders, hyperandrogenism, and abnormalities in ovarian morphology as well as metabolic disorders. PCOS increases the risk of overweight and obesity, diabetes, endometrial cancer, and cardiovascular diseases such as hypertension along with all its long-term consequences. There are limited studies about cardiovascular disorders, especially hypertension, in postmenopausal women with a history of PCOS. The presented paper is an attempt to briefly summarise literature data concerning the influence of this disease on the incidence of hypertension and blood pressure control in postmenopausal women. Women with PCOS more often present features of metabolic syndrome and have increased cardiovascular risk factors including hypertension. The prevalence of hypertension is 2.5 times higher than in corresponding healthy peers. Furthermore, hyperandrogenaemia is associated with elevated blood pressure independent of the patient’s age, insulin resistance, obesity, and dyslipidaemia. In view of this, these patients should be thoroughly screened for hypertensive disorders and educated about the lifestyle modifications that could prevent hypertension later in life.